Combination of High- and Low-Rate GPS Receivers for Monitoring Wind-Induced Response of Tall Buildings - Yi, Zhonghai; Kuang, Cuilin; Wang, Yarong; Yu, Wenkun; Cai, Changsheng; Dai, Wujiao (Sensors (Basel, Switzerland), 2018)
High-rise buildings are susceptible to wind-induced displacements, which can be precisely monitored by using GPS technology. However, GPS monitoring applications may be subject to signal interference and high hardware costs. This study presents a new wind-induced vibration monitoring approach that is based on the mixed use of high-rate and low-rate GPS receivers. In the proposed approach, high-rate receivers are only required in the monitoring stations, where we apply time-differenced positioning to obtain position changes between adjacent epochs. The derived high-rate monitoring station position changes are then integrated with low-rate single epoch relative positioning results between the monitoring and reference stations. Experimental results with both simulated and real data show that the proposed method has a comparable performance with the traditional relative positioning approach, in terms of determining buildings’ vibration frequency, displacement, and acceleration.